(untitled) (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2016)
For the sake of the use of ICT in public education, teacher trainees must experience the functional application of ICT during teaching practice. This study focuses mainly on the teaching practice, where the students can map their own ICT competence and reflect on their strengths and weaknesses. The aim of this research is to examine to what extent the teacher trainees consider themselves competent in the use of ICT tools by the end of their teaching practice. The research used the method of an online questionnaire, whose aim was to examine the ICT-competence of teacher trainees based on teacher competences. The results reflect that teacher trainees use ICT appropriately for teacher-centred activities, but they are not able to make effective, interactive materials for their students. A key factor to progress the students’ ICT competence could be a mentor, a practising teacher at the teaching practice.